Small intestinal microbiota: the neglected stepchild needed for fat digestion and absorption - Chang, Eugene B. (Gut Microbes, 2018)
Our recently published paper “Small Intestine Microbiota Regulate Digestive and Absorptive Adaptive Responses to Dietary Lipids” in Cell Host & Microbe explored the neglected small intestine microbiota and demonstrated its critical role as a regulator of fat digestion and absorption. This work generated the following important take home messages: 1) small intestinal microbes are particularly sensitive to high fat diets and turn on host processes regulating fat digestion and transport, 2) this action is very likely orchestrated by a consortium of microbes, each having different specific effects and targets, and 3) the actions of this consortium appear to be mediated by bacteria-derived small molecules or bioactive components. These findings are expected to provide insight into developing treatments for conditions of under- or over-nutrition. The goal of this addendum is to summarize our findings, address issues related to gut microbiota and gnotobiotic research specifically regarding technology and experimental design, discuss this work in the context of relevant literature, and lastly provide considerations for future research.